Measurement of absolute γ-ray emission probabilities in the decay of 235U. (February 2018) - Marouli, M.; Lutter, G.; Pommé, S.; Van Ammel, R.; Hult, M.; Richter, S.; Eykens, R.; Peyrés, V.; García-Toraño, E.; Dryák, P.; Mazánová, M.; Carconi, P.
Abstract: Accurate measurements were performed of the photon emission probabilities following the α decay of 235 U to 231 Th. Sources of highly enriched 235 U were characterised in terms of isotopic composition by mass spectrometry and their activities were standardised by means of alpha-particle counting at a low defined solid angle. The standardised sources were subsequently measured by high-resolution γ-ray spectrometry with calibrated high-purity germanium detectors to determine the photon emission probabilities. Four laboratories participated in this work and reported emission probabilities for 33 γ-ray lines. Most of them agree with previously published evaluated data. In addition, new values are proposed for γ-lines which have been measured only once in the past. Highlights: Measured gamma-ray emission probabilities per decay of 235 U. Mean values taken from 4 laboratories. Source activity determined by primary standardisation and mass spectrometry. Results reported for 33 γ-ray lines. Generally in good agreement with literature values.